PEMBELAJARAN MENULIS TEKS EKSPLANASI DENGAN MENGGUNAKAN METODE PROBLEM BASED LEARNING BERBASIS APLIKASI POWTOON PADA SISWA SMP KELAS VIII - yuliana, keke; Wikanengsih, Wikanengsih; Suhara, Alfa Mitri (IKIP Siliwangi, 2020)
The purpose of this research are examine the implementation of the problem based learning method based on powtoon application in the learning process to write explanatory texts, so that students be able to solve problems, examine the responses of teacher and students to learning how to write explanatory texts by using the problem based learning method based on powtoon application and examine the difficulties - difficulties is doing the task of writing explanatory texts. The method used descriptive qualitative. Subjects in this research were students at one of the Junior high schools class eight in Mutiara 4 Bandung with a total 36 students. Observation sheets, questionnaire sheets and test sheets are part of the instruments used. The result of this research show the implementation of researcher and students activities that have been observed by observer one and observer two are in accordance with the learning scenarios that have been designed. Questionnaire responses of teacher and students were categorized very well and the average value obtained by students overall was 81.10. On average, categorized as good of student grade. Based on the results, it proves the problem based learning method based on powtoon application is effectively used in the teaching process to write explanatory texts at one of junior high schools class eight in Mutiara 4 Bandung